2021
DOI: 10.1371/journal.pone.0251742
|View full text |Cite
|
Sign up to set email alerts
|

Pre-intervention characteristics of the mosquito species in Benin in preparation for a randomized controlled trial assessing the efficacy of dual active-ingredient long-lasting insecticidal nets for controlling insecticide-resistant malaria vectors

Abstract: Background This study provides detailed characteristics of vector populations in preparation for a three-arm cluster randomized controlled trial (RCT) aiming to compare the community impact of dual active-ingredient (AI) long-lasting insecticidal nets (LLINs) that combine two novel insecticide classes–chlorfenapyr or pyriproxifen–with alpha-cypermethrin to improve the prevention of malaria transmitted by insecticide-resistant vectors compared to standard pyrethroid LLINs. Methods The study was carried out in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 38 publications
8
32
0
Order By: Relevance
“…The indoor and outdoor entomological inoculation rate (EIR) was 21.6 and 5.4 infected bites/person/month, respectively. 25 Study population. A census was carried out in June 2019 in the 123 villages of the study area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The indoor and outdoor entomological inoculation rate (EIR) was 21.6 and 5.4 infected bites/person/month, respectively. 25 Study population. A census was carried out in June 2019 in the 123 villages of the study area.…”
Section: Methodsmentioning
confidence: 99%
“…Details on entomological data collection as well as baseline characteristics have been fully detailed elsewhere. 25 Data management and statistical analysis. All data collected during the survey were recorded in electronic forms on smartphones installed with Open Data Kit (ODK) collect and analyzed with STATA version 16 (Stata Corp LP, College Station, TX).…”
Section: Methodsmentioning
confidence: 99%
“…7 The main vector control consists of the distribution of pyrethroid-only LLINs through universal coverage campaigns every 3 years (the most recent conducted in 2017) and routine service delivery to pregnant women during antenatal care and to children under 5 years during extended programs on immunization. An entomological survey conducted concurrently with this study, 25 showed that Anopheles coluzzii and Anopheles gambiae s . s .…”
Section: Methodsmentioning
confidence: 75%
“…21,28 Indeed, entomological surveys conducted simultaneously to this study have confirmed the scale of pyrethroid resistance with mosquitoes mortality rates at 24h, 48h, and 72h post-exposure lower than 40% for alphacypermethrin and permethrin insecticides and a frequency of the L1014F kdr mutation over 80%. 25 Several studies have also highlighted the increasing role of pyrethroid-resistant Anopheles vectors in malaria transmission. 9,12,14,32 However, this observation might be also related to the age and condition of the nets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation